The sum1-1 mutation affects silent mating-type gene transcription in Saccharomyces cerevisiae. - Livi, G P (1990)
The silent mating-type genes (HML and HMR) of Saccharomyces cerevisiae are kept under negative transcriptional control by the trans-acting products of the four MAR/SIR loci. MAR/SIR gene mutations result in the simultaneous derepression of HML and HMR gene expression. The sum1-1 mutation was previously identified as an extragenic suppressor of mutations in MAR1 (SIR2) and MAR2 (SIR3). As assayed genetically, sum1-1 is capable of restoring repression of silent mating-type information in cells containing mar1 or mar2 null mutations. We show here that the mating-type phenotype associated with sum1-1 results from a dramatic reduction in the steady-state level of HML and HMR gene transcripts. At the same time, the sum1-1 mutation has no significant effect on the level of each of the four MAR/SIR mRNAs.